Solve the following 3 × 3 system. Enter the coordinates of the solution below.
2x – 3y – 2z = 4
x + 3y + 2z = –7
–4x – 4y – 2z = 10

Respuesta :

Step-by-step explanation:

2x - 3y - 2z = 4

[2] x + 3y + 2z = -7

[3] -4x - 4y - 2z = 10

Solve by Substitution :

// Solve equation [2] for the variable x

[2] x = -3y - 2z - 7

// Plug this in for variable x in equation [1]

[1] 2•(-3y-2z-7) - 3y - 2z = 4

[1] - 9y - 6z = 18

// Plug this in for variable x in equation [3]

[3] -4•(-3y-2z-7) - 4y - 2z = 10

[3] 8y + 6z = -18

// Solve equation [3] for the variable z

[3] 6z = -8y - 18

[3] z = -4y/3 - 3

// Plug this in for variable z in equation [1]

[1] - 9y - 6•(-4y/3-3) = 18

[1] - y = 0

// Solve equation [1] for the variable y

[1] y = 0

// By now we know this much :

x = -3y-2z-7

y = 0

z = -4y/3-3

// Use the y value to solve for z

z = -(4/3)(0)-3 = -3

// Use the y and z values to solve for x

x = -3(0)-2(-3)-7 = -1

Solution :

{x,y,z} = {-1,0,-3}

ACCESS MORE